Ethics in AI: how software development companies in Brazil deal with the ethical implications of AI technologies - da Silva, Lucas Gabriel Teixeira; Seno, Eloize Rossi Marques (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2023)
The use of AI technologies has become increasingly common in the software development industry. Although the ethical challenges of using these technologies have been the subject of numerous academic studies, little is known about AI software development practices. Furthermore, there are currently no effective methods and frameworks to help implement ethics at a project level. Given this context, we carried out an empirical study in order to better understand how software development companies in Brazil deal with the ethics of AI in practice. The results highlighted a lack of clarity in standard guidelines and a lack of concern about the ethical implications imposed by the use of AI technologies, suggesting that the governance of AI systems based on principled ethical guidelines is not enough to establish norms to the AI industry and its developers.